Tropical secondary forests in Asia: introduction and synthesis - Jong, W. de; Chokkalingam, U.; Smith, J.; Sabogal, C. (2001)
This paper provides the general objectives of the special issue: secondary forests in Asia: their diversity, importance and role in future environmental management. It provides a brief overview of the renewed attention to tropical secondary forests and sketches the history of research on this subject. The paper introduces two analytical tools that are used throughout this special issue to better understand the current situation and trends of secondary forests in Asia: a typology of tropical secondary forest in Asia, and a conceptual framework that explains the formation and dynamics of these forests. It then outlines some of the main messages that emerge from discussions in the various papers and ends with recommendations for actions and needs for future research.